Ritual purity and the Dead Sea scrolls - Werrett, Ian C. (Studies on the Texts of the Desert of Judah, 2007)
This book represents the first comprehensive study on the concept of ritual purity in the Dead Sea Scrolls since the full publication of the legal material from Qumran. Utilizing an independent approach to the relevant documents from Qumran, this study discusses the primary and secondary literature on the five major categories of impurity in the scrolls (i.e., diseases, clean/unclean animals, corpses, bodily discharges, and sexual misdeeds). This examination is supported by a comparison between the scrolls' purity legislations and their biblical counterparts. The book culminates with a comparison between the purity rulings in the scrolls and a diachronic reading of the explicit agreements and disagreements found therein. The result is a far more comprehensive and nuanced interpretation than has been previously offered.